High neutrophil counts before endovascular treatment for acute basilar artery occlusion predict worse outcomes - Liao, Maofan; Li, Fengli; Hu, Jinrong; Yang, Jie; Wu, Deping; Xie, Dongjing; Song, Jiaxing; Huang, Jiacheng; Tian, Yan; Luo, Weidong; Yue, Chengsong; Liu, Shuai; et al. (Frontiers in Aging Neuroscience, 2022)
Background and purpose Ischemic stroke is related to inflammation. We investigated leukocyte counts, neutrophil counts, and NLR (neutrophil-to-lymphocyte ratio) to explore their prognostic potential and determine if high neutrophil counts before endovascular treatment (EVT) in patients with acute basilar artery occlusion (BAO) are associated with worse outcomes at 90 days post-EVT. Methods Leukocyte and neutrophil counts and NLR were determined in eligible patients from the Acute Basilar Artery Occlusion Study (BASILAR). Patients were divided into four groups according to leukocyte and neutrophil counts and NLR quartiles. The primary outcome was a favorable outcome based on the modified Rankin Scale (mRS: 0–3). The secondary outcome was functional independence (mRS 0–2). The safety outcome was mortality, and an unfavorable outcome was mRS 4–6. Successful reperfusion was mTICI (modified Thrombolysis in Cerebral Infarction) of 2b or 3. All the data were collected within 90 days after EVT. Results We enrolled 586 patients in the study. The leukocyte and neutrophil counts and NLR were significantly associated with clinical outcomes in all patients though no effects were seen in some intervals. Of these three parameters, the neutrophil count had the most significant impact, negatively affecting the outcome. The findings were similar in patients who were successfully recanalized. Conclusion Higher neutrophil counts predicted worse clinical outcomes 90 days after EVT. This finding supports the deleterious role of inflammation in patients with acute BAO despite EVT or successful recanalization.